MARKET JOB REQUIREMENTS FOR INFORMATION TECHNOLOGY PROFESSIONALS IN SAO PAULO CITY (INMR - Innovation & Management Review, 2007)
The current technological development stage, especially in the information technology area, requires imbedded in the set of knowledge of professionals, even as a surviving issue, the development of personal competences and abilities supporting his/her technical expertise. The technical contents taught at information technology courses must follow the directives of Ministry of Education (MEC) and also adapt to the technological evolution of the sector, adjusting contents to the real needs of enterprises and the edge of information technology. In this article, we developed a comparative study between requirements listed in the curriculum directives from MEC and requirements identified in advertisements in daily periodicals and official announcements published. We then proposed a main set of technical abilities required from professionals for the area of information technology.